Language activities for teenagers - Lindstromberg, Seth (Cambridge Cambridge University press, 2004)
Language activities for teenagers has new activities to cajole and tempt teenagers into learning english in a meaningful and enjoyable way. The activities have been specifically designed for use with the 11 - 16 age group.
Contents, references, index.
Keywords: Classroom Techniques; vocabulary; Listening comprehension; Grammar